2010
DOI: 10.1002/hep.23902
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Reduces Liver Damage in a Rat Model of Steatohepatitis: The Underlying Mechanisms and the Role of Polyphenols and Melanoidins

Abstract: Epidemiological data associate coffee consumption with a lower prevalence of chronic liver disease and a reduced risk of elevated liver enzyme levels (c glutamyl transpeptidase and alanine aminotransferase), advanced liver disease and its complications, and hepatocellular carcinoma. Knowledge of the mechanisms underlying these effects and the coffee components responsible for these properties is still lacking. In this study, 1.5 mL/day of decaffeinated coffee or its polyphenols or melanoidins (corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 29 publications
10
145
2
7
Order By: Relevance
“…Paur et al [29] showed that extracts of dark-roasted coffee inhibit NF-κB activity by more than 80%, in LPS-induced NF-κB activation. Similar evidences were reported by Vitaglione et al [38] on reducing TNF-α expression.…”
Section: Anti-inflammatory Activitysupporting
confidence: 79%
“…Paur et al [29] showed that extracts of dark-roasted coffee inhibit NF-κB activity by more than 80%, in LPS-induced NF-κB activation. Similar evidences were reported by Vitaglione et al [38] on reducing TNF-α expression.…”
Section: Anti-inflammatory Activitysupporting
confidence: 79%
“…Hs-CRP is synthesized predominantly in the liver and its serum levels may be more closely linked to the extent of hepatic inflammation (45). In a high-fat-diet (HFD)-induced NASH model in male Wistar rats, Vitaglione et al showed that coffee in drinking water significantly improved levels of glutathione and malondialdehyde (46).…”
Section: Discussionmentioning
confidence: 99%
“…Yamauchi et al (2010) reported that the reduction in the level of liver fat was a consequence of decreased gene expression related to fatty acid synthesis in the liver. Another study found that coffee consumption had a protective effect on liver damage caused the fatty diet, mediated by a reduction in hepatic fat accumulation by increasing beta-oxidation of fatty acids (Vitaglione et al 2010).…”
Section: Resultsmentioning
confidence: 97%